Naelofar Hijab / Intan Shafinie Sahat ... [et al.] - Sahat, Intan Shafinie; Abd Aziz, Intan Aziana; Mordin Chee, Syaza Nabilah Chee; Wira, Noorshahhirah (2016)
Naelofar is a partnership business with a small team of trusted and like-minded members. Neelofa and new partners decided to revolutionize and simplify modest fashion to make shawls more practical and easier to wear. After countless brainstorming sessions, trials and errors, they succeed in producing an instant shawl and launched Naelofar hijab in 2014. They started selling the shawl online and at bazaar. The sales at the beginning grow slowly as people are not aware of the product. The demand for the hijab are very low. The product may be unknown to certain customers and they need a heavy promotional and advertising activity designed to raise awareness of the instant hijab. In this stage, they only have a few competitors such as BawaI Adijuma, a square head scarf which is the most popular and commonly used by muslimah consumers at that time.